2014
DOI: 10.1080/10298436.2014.960998
|View full text |Cite
|
Sign up to set email alerts
|

An overview of various new road profile quality evaluation criteria: part 2

Abstract: This is the second part of an article which correlates road-induced impacts on vehicle to a selection of road assessment criteria. The impacts on tyre, suspension and radiator wear are studied by running a multibody semi-trailer truck model on 270 road profiles. The model accurateness is assessed by comparing international roughness index (IRI) -impact relationships to those published in the literature. A new profile rating method uses wavelength content to predict the impacts of a specific profile on driver a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…ISO 2631-1 specified for the feet vibration of a seated person, that is, the vehicle cab floor, the same filer W k in the vertical ( z -) axis. Gagnon et al ( 24 ) confirmed Equation 4 and stated that the ratio of the ISO-weighted acceleration at the floor of the reference quarter-car simulation model traveling at 100 km/h to the IRI was a linear monomial with a slope coefficient between 0.16 and 0.19.…”
Section: Relation Linking Road Roughness Vehicle Speed and Vibrationmentioning
confidence: 95%
“…ISO 2631-1 specified for the feet vibration of a seated person, that is, the vehicle cab floor, the same filer W k in the vertical ( z -) axis. Gagnon et al ( 24 ) confirmed Equation 4 and stated that the ratio of the ISO-weighted acceleration at the floor of the reference quarter-car simulation model traveling at 100 km/h to the IRI was a linear monomial with a slope coefficient between 0.16 and 0.19.…”
Section: Relation Linking Road Roughness Vehicle Speed and Vibrationmentioning
confidence: 95%
“…In contrast, the factor vehicle type was shown to exert a reasonable influence on all roughness indexes (IRI, Half-car IRI and FRI). Gagnon et al (2014Gagnon et al ( , 2015 compared the results for IRI, Half-car IRI, FRI and vibration response on a tractortrailer model. Reza et al (2005) presented development of a new performance index for pavements that incorporates aspects of ride quality together with surface distress, for possible adoption by Ohio Department of Transportation.…”
Section: Full-car Roughness Indexmentioning
confidence: 99%
“…A linear combination of the RIF from different speed bands produces a time-wavelength-intensity transform (TWIT) that, unlike the IRI, is wavelength-unbiased. Gagnon et al (2014Gagnon et al ( , 2015 compared 19 road roughness indexes and vibration response on the truck-trailer model. All evaluated road indexes were based on the reference QCM intended for IRI simulation.…”
Section: Other New Approachesmentioning
confidence: 99%